(untitled) (Indian Journal of Animal Production and Management, 2024)
An investigation was conduct to study the constraints perceived by women dairy farmers and veterinarians on dairy farming in Guntur district of Andhra Pradesh. In technical constraints, majority (94.70%) of women dairy farmers in Narasaraopeta division perceived lack of preservation facility for milk as major constraint whereas majority (85.30%) of women dairy farmers in Guntur division perceived lack of preservation facility for milk as major constraint and majority of women dairy farmers (76.00%) in Pedaravuru division perceived low milk production by local breeds and lack of knowledge in identifying diseases of animals as major constraints. In economic constraints, 90.70% of women dairy farmers in Pedaravuru division perceived high cost of concentrate and other feeds as major constraint whereas 64.00% in Narasaraopeta division perceived low market price for milk as major constraint. and 58.70% in Guntur division perceived low market price for milk as major constraint. Overall majority of farm women (68.44%) in the study area perceived lack of preservation facility for milk was the major technical constraint. Low market price for milk was the major economic constraint perceived by farm women (60.90%) in the study area. It was observed that 75.56% of veterinarians perceived high investment for establishing an entreprise as major constraint in the study area.